Analisis Pelaksanaan Otonomi Khusus dalam Mengatasi Kemiskinan di Kabupaten Aceh Barat - Siti Ramazan; Safrida Safrida (Publisia: Jurnal Ilmu Administrasi Publik, 2022)
The implementation of special autonomy in West Aceh Regency has been carried out well, this can be seen from the various efforts made by the government in tackling the problems that exist in the community, especially the problem of poverty alleviation. Poverty is a point where people are unable to meet basic needs in maintaining a better life. So this study aims to analyze the implementation of special autonomy as a whole in West Aceh Regency in an effort to alleviate poverty, therefore an in-depth analysis is needed in order to achieve good results. This research uses qualitative methods through a case study approach, data collection techniques are carried out through observation, interviews, documentation, and literature studies. Data analysis was carried out through data reduction, data display, and drawing conclusions. Based on the findings in the field, it shows that the people of West Aceh Regency are still in a high poverty level, namely 18.34%. The conclusion of this study states that the implementation of special autonomy as an effort to alleviate poverty has not yet fully run optimally in West Aceh Regency, because there are still many inequalities from the regional government in distributing special autonomy funds to each district/city. In this case, districts/cities only get 40%, and the other 60% is managed by the province. Thus, the special autonomy fund used for poverty alleviation is only 5% of 40% in Aceh Barat District